Answer:
A.)
2 * 3 = 6
6 * 3 = 18
18 * 3 = 54
54 * 3 = 162
B.) The answer is 3x more, each step goes up times 3.
As you can see, 2 is the first term in the sequence. Multiplying the current term by the common ratio, which is 3, presents the next term. Then that term is multiplied by the common ratio to present the term after it.
an + 1 = 3an
or you can write
an = 3an - 1
where:
an is the new term ,
an - 1 is the preceding term
Notice that we can write the following formula as :
an / (an - 1) = 3
This shows that the ratio between the new term to preceding term is 3.
Hope this helps.